Perspectives on death and dying: a study of resident comfort with End-of-life care - Schmit, Jessica M. (BMC Med Educ, 2016)
BACKGROUND: Despite the benefits to early palliative care in the treatment of terminal illness, barriers to timely hospice referrals exist. Physicians who are more comfortable having end-of-life (EOL) conversations are more likely to refer to hospice. However, very little is known about what factors influence comfort with EOL care. METHODS: An anonymous survey was sent to all the residents and fellows at a single institution. Self-reported education, experience and comfort with EOL care was assessed. Using multivariate logistic regression analysis, variables that influenced comfort with EOL conversations were analyzed. RESULTS: Most residents (88.1%) reported little to no classroom training on EOL care during residency. EOL conversations during residency were frequent (50.6% reported > 10) and mostly unsupervised (61.9%). In contrast, EOL conversations during medical school were infrequent (3.7% reported >10) and mostly supervised (78.6%). Most (54.3%) reported little to no classroom training on EOL care during medical school. Physicians that reported receiving education on EOL conversations during residency and those who had frequent EOL conversations during residency had significantly higher comfort levels having EOL conversations (p = 0.017 and p = 0.003, respectively). Likewise, residents that felt adequately prepared to have EOL conversations when graduating from medical school were more likely to feel comfortable (p = 0.030). CONCLUSIONS: Most residents had inadequate education in EOL conversation skills during medical school and residency. Despite the lack of training, EOL conversations during residency are common and often unsupervised. Those who reported more classroom training during residency on EOL skills had greater comfort with EOL conversations. Training programs should provide palliative care education to all physicians during residency and fellowship, especially for those specialties that are most likely to encounter patients with advanced terminal disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-016-0819-6) contains supplementary material, which is available to authorized users.